Transition to self-management among emerging adults with type 1 diabetes: a mixed methods study - Vitale, Rebecca J.; Asher, Noa; Shank, Kaitlyn; Katyal, Biren; Tinsley, Liane J.; Garvey, Katharine C.; Laffel, Lori M. B. (Frontiers in Clinical Diabetes and Healthcare, 2024)
IntroductionEmerging adulthood is challenging for young people with type 1 diabetes (T1D). This study evaluated transition to diabetes self-management and perceptions of care transfer using mixed methods.MethodsAn online survey queried demographics, management characteristics, diabetes knowledge, self-care readiness, adherence, and diabetes distress. T-tests compared survey scores between those with self-reported target A1c <7.0% versus ≥7.0%. Pearson correlations assessed associations between A1c and diabetes distress, stratified by A1c <7.0% versus ≥7.0%. Qualitative semi-structured interviews elicited perceptions of young adults; transcripts were analyzed using directed qualitative content analysis.ResultsOf 141 participants (30% male, 84% non-Hispanic white) completing the survey, 41% self-reported target A1c <7.0%. Diabetes knowledge and self-care readiness scores did not differ between those with A1c <7.0% versus ≥7.0%, while diabetes distress was lower (45 ± 20 vs 52 ± 20, p=0.01) and adherence higher (77 ± 12 vs 71 ± 14, p=0.02) in those with A1c <7.0% versus ≥7.0%. Diabetes distress was significantly associated with glycemic outcomes in those reporting A1c ≥7.0% (R=0.36, p<0.01). Qualitative analysis (24 participants) revealed five themes and two sub-themes, notable for need for more mental health support, support from others with T1D, benefits of technology for care autonomy, and challenges of obtaining diabetes supplies.DiscussionEmerging adults with self-reported target A1c endorsed lower diabetes distress and higher adherence than those with elevated A1c. Mental health access, support from others with T1D, technology use, and guidance for supply acquisition may improve transition to self-management and care transfer for emerging adults with T1D.